The formation methodics of skills of analytical thinking through the development of mathemathical competencies in the students of elementary schools - Saidovna, Djurayeva Perdegul (Middle European Scientific Bulletin, 2021)
Formation of analytical thinking skills through the development of mathematical competences in primary school students, the use of collaborative and intensive methods, orientation to full coverage of the effectiveness of teaching mathematics on the basis of the application of innovative techniques, innovation technologies, mastering of new knowledge, skills and competences in the field.